Tenecteplase versus alteplase for acute ischaemic stroke: a meta-analysis of phase III randomised trials - Yongjun Wang; Yunyun Xiong; Yuesong Pan; Shuya Li; Kai-Xuan Yang; Liyuan Wang; Guangshuo Li; Manjun Hao (Stroke and Vascular Neurology)
Background Tenecteplase (TNK) was found non-inferior to alteplase in recent clinical trials. We aimed to elucidate the efficacy and safety of TNK versus alteplase for acute ischaemic stroke (AIS).Methods Systematic literature search and a meta-analysis of phase III clinical trials in ischaemic stroke patients with TNK use were conducted. The primary outcome was excellent functional outcome which was defined as modified Rankin Scale score of 0–1 at 90 days and safety outcomes included symptomatic intracerebral haemorrhage and death at 90 days. We used random-effects model to estimate the pooled risk difference and 95% CI in R package ‘Meta’. The included trials were adapted to the non-inferiority analysis with a margin of −4%.Results Three trials enrolling 4094 patients were identified by systematic search. All trials included AIS patients within 4.5 hours time window. Meta-analysis indicated that 1089 (53.0%) of 2056 patients in the TNK arm and 1016 (50.5%) of 2012 in the alteplase arm had excellent functional outcome at 90 days (0.03 (95% CI −0.00 to 0.06); I2=0%), meeting the prespecified non-inferiority threshold. And TNK thrombolysis was not correlated with increased risk of symptomatic intracerebral haemorrhage (0.00 (95% CI −0.01 to 0.01); I2=0%) or death (0.01 (95% CI −0.01 to 0.02); I2=0%) at 90 days. The sensitivity analysis with the 0.25 mg/kg trials exclusively showed similar results to the main analysis.Conclusions TNK was non-inferior to alteplase for achieving excellent functional outcome at 90 days without increasing the safety concern in treating patients with AIS. These findings suggest that TNK can be an alternative to alteplase.PROSPERO registration number CRD42022354342.